A Longitudinal Pilot Study for Examining Symptom Reduction in Patients With Cancer in a Palliative Care Program: A Primarily Rural Northeast Texas Population. Issue 2 (3rd April 2019) - Orsak, Gabriela; McGaha, Paul; Brandon, Paula; Swan, Amy; Singh, Karan P.
Abstract: Many patients with cancer live in rural areas and research is lacking on the efficacy of palliative care programs in rural community settings. This pilot study was conducted in a primarily rural setting where healthcare professionals delivered palliative care to 52 mostly lower income patients with a variety of cancers. They were assessed for physical, financial, psychosocial and overall symptom intensity at baseline and at three consequent assessments. This pilot study demonstrated the potential efficacy of an outpatient palliative care program in a mostly rural setting in the reduction of physical, psychosocial, and overall symptom intensity in patients with cancer.